2019
DOI: 10.1002/jper.18-0195
|View full text |Cite
|
Sign up to set email alerts
|

A disintegrin‐like and metalloproteinase with thrombospondin‐1 (ADAMTS‐1) levels in gingival crevicular fluid correlate with vascular endothelial growth factor‐A, hypoxia‐inducible factor‐1α, and clinical parameters in patients with advanced periodontitis

Abstract: Background ADAMTS (a disintegrin‐like and metalloproteinase with thrombospondin) are a family of proteinases that are structurally similar to the family of matrix metalloproteinases with critical roles in damage and repair of the extracellular matrix. Their functions are closely related to inflammation, hypoxia, and vascularization. Our aim was to determine levels of ADAMTS‐1 in gingival crevicular fluid (GCF) in patients with advanced periodontal diseases and identify their association with hypoxia‐inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…HIF‐1α protein expression was found to be markedly increased in chronically inflamed gingiva adjacent to periodontal pockets in patients with periodontitis 18,19 . GCF HIF‐1α levels were higher in G‐AgP patients compared to those of periodontally healthy individuals 20,21 . In consistent with the findings from these studies, 20,21 increased GCF HIF‐1α levels in G‐AgP group might suggest involvement of HIF‐1α with increased gingival inflammation and deeper periodontal pockets in those patients.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…HIF‐1α protein expression was found to be markedly increased in chronically inflamed gingiva adjacent to periodontal pockets in patients with periodontitis 18,19 . GCF HIF‐1α levels were higher in G‐AgP patients compared to those of periodontally healthy individuals 20,21 . In consistent with the findings from these studies, 20,21 increased GCF HIF‐1α levels in G‐AgP group might suggest involvement of HIF‐1α with increased gingival inflammation and deeper periodontal pockets in those patients.…”
Section: Discussionsupporting
confidence: 84%
“…have reported that G‐AgP and chronic periodontitis patients had significantly higher GCF HIF‐1α levels than periodontally healthy controls. These findings suggest a possible association of HIF‐1α with the pathophysiology of periodontal inflammation 18‐21 . As HIF‐1α, under hypoxic condition, upregulates primer angiogenic mediator vascular endothelial growth factor (VEGF) 22,23 which is closely related to periodontal inflammation, wound healing and alveolar bone remodeling, 24‐26 TNF‐α increases HIF‐1α and its downstream effector VEGF in an oxygen‐independent manner 27,28 .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations